Questioning one-size-fits-all dialysis prescription: balancing dialysis prescription and residual kidney function - João Fernandes; Anabela Soares Rodrigues (Bulletin de la Dialyse à Domicile, 2023)
Recent awareness of the viability and benefits of incremental hemodialysis is an opportunity to review clinical practices and improve the process of dialysis induction. Incremental dialysis is a standard approach in peritoneal dialysis prescription, with a focus on the quality parameter of nephroprotection. The same should apply in hemodialysis, with individualization of the prescribed extracorporeal technique: frequency, duration and intensity, in either home or center hemodialysis, are prescription variables to adjust according to the patient’s residual renal function, medical condition and psycho-social priorities. Considering that fluid balance and smooth ultrafiltration critically impact patient survival, incremental dialysis schedules need to be carefully tailored and grounded in routine residual kidney function measurement. This paper raises concerns about both the benefits of incremental dialysis and its putative detrimental effects, these being mainly dependent on the quality of the hemodialysis prescription and external economic constraints. As a comparator, incremental peritoneal dialysis is a scientifically based model to pursue, whichever the modality, based on updated concepts of patient-centered prescription and adequacy in dialytic renal replacement therapies.